João Carlos Teixeira Brandão, the first Brazilian professor of Psychiatry - Mathias, Cátia; Nardi, Antonio E. (Arquivos de Neuro-Psiquiatria, 2018)
Aim: To describe the highlights in the personal, professional, and political life of the first Brazilian Professor of Psychiatry.Methods: The article draws on a wide range of documents: newspaper articles, documents of Brazilian medical institutions, scientific articles, theses, and books.Results: João Carlos Teixeira Brandão was a distinguished 19th-century Brazilian psychiatrist and leader of the institutionalization and consolidation of the field of Psychiatry in Brazil. He contributed to the recognition of the professional jurisdiction of the “alienist”, a specialized professional, qualified in clinical practice, diagnosis, and the definition of the boundaries between sanity and madness, based on scientific criteria, in the late 19th and early 20th centuries.Conclusion: This article highlights the key moments in the professional and political career of Professor João Carlos Teixeira Brandão, from his graduation from the Rio de Janeiro School of Medicine in 1877 to his death in 1921, when he was still active in national politics.
Keywords: Psychiatry; mental disorders; history of Medicine